Production of Lipase by P. fluorescens (NRLL B-2641) under Submerged Fermentation Conditions - Tanyol, Mehtap; Uslu, Gulsad (Dr M N Khan, 2014)
Lipases are industrially important enzymes produced by a great variety of microorganisms. In this study, the production of extracellular lipase by Pseudomonas fluorescens (NRLL B-2641) using submerged fermentation was studied: The effects of. initial pH, carbon source, nitrogen source and metal ion addition on lipase activity were investigated using batch experiments. The highest enzyme activity and biomass production obtained were 2.50 U mL(-1) and 2.95 g cell dry wt. L-1, respectively, using a fermentation medium with 1% corn oil as the carbon source, 0.4% peptone as the nitrogen source and an initial pH of 6.0. The addition of calcium increased the enzyme activity to 3.30 U mL(-1). Thus, initial lipase activity, which was 0.92 U mL(-1), increased 356%. Partial characterization of crude lipase was performed to determine the optimum pH and temperature. The crude lipase displayed high activities at pH 6.0-8.5 and 35-65 degrees C, with maximum activity at pH 8.0 and 50 degrees C.
Keywords: Extracellular Lipase; Alkaline Lipase; Psychrotrophic Bacteria; Culture-Conditions; Carbon-Sources; Stable Lipase; Pseudomonas; Purification; Growth; Optimization